Siapkah Indonesia Menghadapi Inovasi Sistem Pembayaran? - Sastriani, Sastriani (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
This study discusses the non-cash payment system and inflation effects to economic growth in Indonesia from 2010 to 2019 period. The dependent variable in this study is economic growth which is calculated through GDP. While the independent variables are Debit/ATM cards, credit cards, and inflation. The method in this research is multiple linear regression analysis using the Ordinary Leasrt Square (OLS) model. Multiple linier analysis is a method to determine the relationship of several independent variables and the dependent variable. Then, to determine the directions which is a positive or negative relation. The date were processed using W-views 10 software. The results of this study indicate that credit/ATM cards are positively related and significant to economic growth. While credit cards and growth were negative and significant to economic growth.